Elementary School Teachers’ Insight to Rotation Models of Blended Learning - Anjarani, Devie Reztia; Yuliarsih, Yuliarsih; Tafrilyanto, Chairul Fajar; Harsono, Harsono (Universitas Muhammadiyah Gresik, 2024)
Blended learning, which is mostly used in higher education, is introduced to Elementary Schools teachers through teaching and learning English. This study aimed at exploring the teachers’ responses on their attitudes towards the implementation of blended learning as an interactional teaching and learning tool in English course. Observation, questionnaire, and interview were given to 24 elementary school teachers who are also students of English in Open University. The result showed around 45.8% of them have already had PC or laptop and only 8.2% really have problem in internet connection. Further, 50% of teachers stated that rotation blended learning is ease their teaching and learning.